Model pembelajaran creative problem solving terhadap keterampilan generik sains pada materi biologi - Suryaningsih, Yeni; Muhapilah , Selpi; Lafiah, Mas'atun (Papanda Publisher, 2024)
This research was motivated by problems in implementing the learning methods applied by teachers who still emphasized memorizing concepts, resulting in a lack of students' ability to think for problem solving. The aim of this research is to apply a creative problem solving learning model to improve students' generic science skills. The research subjects were class X MIPA students at SMAN 1 Sukahaji. The research design uses a pretest posttest control group design which is analyzed by calculating the N-gain value. The research instrument is a multiple choice test and essay using generic science skill indicators. The results of research using N-gain calculation analysis showed an increase in the average pretest posttest score for the experimental class from 48.1 to 80.8, while for the control class from 42.6 to 71.2. This shows that there is an increase in both classes, but the increase in the experimental class is higher than the control class, meaning that applying the creative problem solving learning model can be used as a solution as an effort to help improve generic science skills. Keywords: Creative Problem Solving Learning Model, Generic Science Skills.